2012
DOI: 10.1016/j.polymertesting.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling of mode I delamination specimens by means of implicit and explicit solvers

Abstract: The simulation of delamination using the Finite Element Method (FEM) is a useful tool to analyse fracture mechanics. In this paper, simulations are performed by means of two different fracture mechanics models: Two Step Extension (TSEM) and Cohesive Zone (CZM) methods, using implicit and explicit solvers, respectively. TSEM is an efficient method to determine the energy release rate components G Ic , G IIc and G IIIc using the experimental critical load (P c ) as input, while CZM is the most widely used method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Hence, the value of 410 6 MPa/mm was a good choice because it could be easily estimated using Equation (5). This was also in the similar range of the values generally used by researchers [22,29,30,35]. From the above parametric studies, the suggested cohesive parameters for accurate simulation with reasonable computational time were le = 0.5 mm, tu,III = 80 MPa, Dv = 110 -3 and kIII = 410 6 MPa/mm.…”
Section: Peak Load (N) Peak Load (N)mentioning
confidence: 76%
See 2 more Smart Citations
“…Hence, the value of 410 6 MPa/mm was a good choice because it could be easily estimated using Equation (5). This was also in the similar range of the values generally used by researchers [22,29,30,35]. From the above parametric studies, the suggested cohesive parameters for accurate simulation with reasonable computational time were le = 0.5 mm, tu,III = 80 MPa, Dv = 110 -3 and kIII = 410 6 MPa/mm.…”
Section: Peak Load (N) Peak Load (N)mentioning
confidence: 76%
“…Thus, the initial estimation of kIII was 410 6 MPa/mm. This is in the similar range of the values generally used by researchers [22,29,30,35]. To study the effects of interface stiffness on the numerical force-displacement response, the range between 410 5 -410 8 MPa/mm was considered.…”
Section: Guidelines Of Cohesive Parameter Selectionmentioning
confidence: 97%
See 1 more Smart Citation
“…These parameters are chosen for illustration purpose. The bi-linear shape is chosen because this is the shape most commonly used in FEM when delamination is included [4,7,[34][35][36][37]. The value of the critical separation used in these simulations is much smaller than the value determined earlier from the experiments (here was about 3 mm), but is of the order of magnitude corresponding to the parameters describing the crack tip fracture energy.…”
Section: Numerical Approach and Resultsmentioning
confidence: 99%
“…To avoid interpenetration between the upper and lower arms, contact surfaces are defined at the adjacent surfaces of the interface using frictionless contact. An element thickness of 10 µm is used for the cohesive elements [ 15 , 23 ], which is also in the same order of the resin-rich region [ 24 ] and the Teflon thickness. The delamination zone is meshed with 0.1 mm element size, while the region outside the delamination zone is meshed with mesh size of 2 mm.…”
Section: Numerical Simulationmentioning
confidence: 99%